Genealogical characteristics of children and adolescents with cholelithiasis and their families - Shutova, O. V.; Bahatska, N. V. (Zaporozhye Medical Journal, 2018)
One of the common pathologies of the hepatobiliary tract is cholelithiasis. The prevalence of this disease among children and adolescents is of particular concern. The purpose of the study is to identify the family aggregation of the hepatobiliary pathology and other multifactorial diseases in the pedigrees of children and adolescents with cholelithiasis. Materials and methods. Genealogical analysis was performed in 105 families with sick children aged from 2 to 17 years who were examined and treated for hepatobiliary tract disorders in gastroenterological and somatic departments. The comparison group comprised 75 family pedigrees of peers, inhabitants of the Kharkiv region, who were not diagnosed with cholelithiasis and other serious non-communicable diseases. Results. Gastroduodenal pathology ranked first among the families of sick children in the morbidity prevalence patterns in terms of gastrointestinal tract pathology (14.29 % vs. 6.19 % in relatives of healthy children, P < 0.001), followed by cholelithiasis (13.19 % vs. 0.44 % in relatives of healthy children, P < 0.001), and other diseases of the hepatobiliary system ranked third – (7,21 % vs. 5,59 % in relatives of healthy children, P > 0.05). In our studies, the calculation of cholelithiasis formation depending on the gender identity of sick children relatives also confirmed that in the female subjects the risk of cholelithiasis was 6.7 times increased compared with the male population (OR = 6.69; CI = 3.71–12.06; p < 0.05). Diseases such as cholelithiasis and other diseases of the hepatobiliary system, gastroduodenal pathology and cardiovascular disorders prevailed among the first-degree relatives of children suffering from cholelithiasis in comparison with these diseases diagnosis in relatives of healthy children. Conclusions. Based on the family pedigree analysis of patients and healthy children, an inherited predisposition to cholelithiasis was determined in 63.81 % of sick children families, and it was 15.9 times higher than the incidence of this disease in healthy children families, thus made it possible to consider this indicator as a prognostic sign for cholelithiasis development. Familial aggregation of cholelithiasis, other diseases of the hepatobiliary system and gastroduodenal pathology in the first-degree relatives; cholelithiasis and gastroduodenal pathology in the second-degree relatives; cholelithiasis in the third-degree relatives was revealed compared with the frequency of these diseases in healthy children families. The maternal inheritance of cholelithiasis was found more frequently than paternal and both maternal and paternal. The odds ratio (OR) value in the presence of cholelithiasis in the sick children families was 24.7 times increased; 2,6 times – in the presence of gastroduodenal pathology; 1.5 times – in the presence of other diseases of the hepatobiliary system compared with the frequency of these diseases in healthy children families; and 6.7 times for females.